Effects of a 28-day "Living high - training low" on T-lymphocyte subsets in soccer players - Zhang, Y.; Hu, Y.; Wang, F. (International Journal of Sports Medicine, 2007)
The purpose of this study was to investigate the changes in T-lymphocyte subsets in soccer players during "living high - training low" (LHTL) for 28 days in comparison to equally trained control players. Sixteen male soccer players were randomly assigned into two groups. The LHTL group lived in normobaric hypoxic rooms, simulating an altitude of 3000 m for 10 hours per night for 28 days. The control group lived at sea level. Both LHTL and control groups trained together at sea level and completed the same training schedules. The blood samples were collected prior to the trial (baseline) and at 1, 14, 21 and 28 days of the trial, respectively. Lymphocyte subsets were quantitated using the recommended flow cytometry method. The results showed that the relative changes from the baseline in the CD4+/CD8+ ratio, in both LHTL and control groups, followed a similar downward trend during the trial. However, the trend was more pronounced in the LHTL group. In the LHTL group, significant differences were seen at both 14 and 28 days compared to the baseline. In addition, a significant difference was also observed between the groups at 14 days. During LHTL, hypoxia may augment the effect which training may have on T-lymphocyte subsets after 14 days, even when training was not performed under hypoxic condition. The long term effect of LHTL was unknown at this time and needs further investigation.